General aspects of trigeminal neuralgia: Guidelines for clinical approach and neurosurgical intervention (Research, Society and Development, 2023)
Trigeminal neuralgia is a disease that affects the V pair of cranial nerves, which are trifurcated in the face and sensitize, ipsilaterally, the corresponding hemiface. The character of excruciating pain with excruciating pain makes this pathology a relevant object of study, given its epidemiology, including extremes in suicidal outcomes. The objective of the study is to substantiate and clarify the main aspects of the pathophysiology of trigeminal neuralgia, which have not yet been fully evidenced, and from that, to organize its information in a concise and efficient content for informational support. The present work deals with an integrative literature review that used the Scielo database, as a theoretical foundation, answering the guiding question. Using the PECO research method, 146 articles were found, which were carefully selected and read. In view of this, treatment with anticonvulsants proved to be quite effective for most cases, as the pathophysiology of the disease supports the effectiveness of pharmacological treatment. However, there is a group of patients who do not respond to pharmacological interventions and need surgical intervention for therapeutic improvement. Therefore, a range of therapeutic proposals is created based on the most varied neurosurgical techniques, such as vascular decompression, radiosurgery, rhizotomy with glycerol, among others. Therefore, the option for a certain treatment depends on several aspects related to the patient in question: the composition of the multidisciplinary team, failure of non-invasive therapy and which resources will be used, seeking the complete restoration of health or substantial improvement.